MERESPON LGBTIQ DITINJAU BERDASARKAN HUKUM PIDANA ISLAM - Sultan Deyis, Muhammad Furqan; Azizi, Kemal (Journal of Islamic Law Studies, 2021)
Lesbian, Gay, Bisexual, Transgender, Intersexual, Queer (LGBTIQ) is a phenomenon that spreads in the modern era as a form of sexual deviation which is strongly influenced by wrong parenting, inadequate Islamic religious education, bad social relations, and factors from poor information and communication obtained from social media. The growth and development of children include important aspects that must be balanced and directed proportionally. Aspects of children's growth and development include: spirituality (faith), physical (physical), psychological (psychic), intellectual, emotional, moral, social, sexual, and economic should be balanced with each other. If parents and teachers can balance these aspects of education, understanding and awareness will be achieved about the dangers posed by LGBTIQ behavior. Therefore, the role of parents and teachers in understanding the dangers of LGBTIQ for the younger generation is very much needed. This journal was created to provide an understanding to modern society about the bad behavior of LGBTIQ which has an impact on the survival of the community, both in terms of association with fellow people and human relations with Allah SWT in Islamic law. Of course, all the actions carried out by humans will be accountable to the creator later, both in this world and in the hereafter. Where LGBTIQ itself is an act that is forbidden in Islamic law. Therefore, here the author will focus more on this journal about LGBTIQ and its views both in Islamic law (Islamic criminal law) and social interaction in Islam.